Screening the CALIBR ReFRAME Library in Search for Inhibitors of Candida auris Biofilm Formation - Wall, Gina; Chen, Emily; Hull, Mitchell V.; Lopez-Ribot, Jose L. (Frontiers in Cellular and Infection Microbiology, 2020)
Candida auris is an emerging yeast which, since its first isolation about a decade ago, has spread rapidly and triggered major infectious outbreaks in health care facilities around the world. C. auris strains often display resistance to clinically-used antifungal agents, contributing to high mortality rates. Thus, there is an urgent need for new antifungals to contain the spread of this emerging multi-drug resistant pathogen and to improve patient outcomes. However, the timeline for the development of a new antifungal agent typically exceeds 10-15 years. Thus, repurposing of current drugs could significantly accelerate the development and eventual deployment of novel therapies for the treatment of C. auris infections. Towards this end, in this study we have profiled a library of known drugs encompassing approximately 12,000 clinical-stage or FDA-approved small molecules in search for known molecules with antifungal activity against C. auris; more specifically, those capable of inhibiting C. auris biofilm formation. From this library, 100 compounds displaying antifungal activity were identified in the initial screen, including 26 compounds for which a dose-response relationship with biofilm-inhibitory activity against C. auris could be confirmed. Of these, 5 were identified as the most interesting potential repositionable candidates. Due to their known pharmacological and human safety profiles, identification of such compounds should allow for their accelerated preclinical and clinical development for the treatment of C. auris infections.